A Research on Developmental Characteristics of Children With Language Delay in Zhejiang Province, China - Yao, Dan; Zeng, Yan; Gao, Minjie; Shen, Jiyang; Zhan, Jianying; Zhao, Zhengyan (Frontiers in Pediatrics, 2020)
Objective: To discuss and explore the developmental characteristics of one to four-year-old children with language delays in Zhejiang Province, and to provide scientific basis for early clinical detection and comprehensive intervention. Methods: Assess 1113 children between the ages of 1 and 4 with language delays who were treated in the author’s hospital using sign—significant reactions (S-S). These children were divided into six groups, with each group having an age difference of six months. The developmental characteristics of each group were analyzed and described. Results: 1) Children from the age of 18 months to 36 months were most likely to be affected by language problems. While boys were more susceptible than girls in each group. 2) There was no significant difference in the proportion of children with poor communication attitude among each group. 3) The older the group was, the higher the proportion of basic learning ability abnormality. The cut-off age for qualitative leap in the proportion of basic learning abilities was 2 years old. 4) With the increase of age, the proportion of abnormal language comprehension in each group increased gradually. The cut-off age for qualitative leap in the proportion of language comprehension was 1.5 and 2 years old. Conclusion: Language delays usually occur in children around the age of two, and as the children get older, in addition to expression language abilities, they’re more likely to have abnormal language understanding abilities and abnormal basic learning abilities. Based on the clinical research, we must take early screenings for this age group seriously and conduct intervention training as soon as possible.